An explicit description of the second cohomology group of a quandle - Garcia Iglesias, Agustin (2016)
We use the inflation-restriction sequence and a result of Etingof and Graña on the rack cohomology to give a explicit description of 2-cocycles of finite indecomposable quandles with values in an abelian group. Several applications are given.